Appointing Extremists. (2nd November 2017) - Bailey, Michael A.; Spitzer, Matthew
Abstract: Given their long tenure and broad powers, Supreme Court justices are among the most powerful actors in American politics. In this paper, we present a model of the nomination process that highlights the how uncertainty about a potential justice's preferences can lead a president to prefer a nominee with extreme preferences. In certain cases, Senators may also prefer extreme nominees, leading to the nomination and confirmation of justices whose preferences seem to diverge from those of elected officials. While our focus in this paper is on the Supreme Court, the analysis extends in many ways to other multimember appointed bodies as well.